Cerebral venous sinus thrombosis: clinical and neuroradiological analysis of 10 consecutive cases at hospital México between january and december 2013. - Rosales Bravo, Luis Guillermo (2018)
Cerebral venous sinus thrombosis (CVST) is an uncommon and potentially life -threatening neurological emergency. The annual incidence is estimated at 2 -7 cases/million population. The sudden occlusion with a clot into a venous sinus causes an acute increase of the intracranial pressure rising to intracranial hypertension. Due to the rupture of cortical veins both parenchymal brain hemorrhage and subarachnoidal hemorrhage can be present in the initial unenhanced brain CT scan. Its diagnosis can be a challenge. High clinical suspicious is mandatory for an early diagnostic. Nowadays, with the use of CT and CTV its diagnosis is less difficult. Most of the patients recover without any neurological impairment. In CVST the rapid initiation of anticoagulant treatment is mandatory in order to reopen the occluded venous sinus. Neither the parenchymal brain hemorrhage nor the subarachnoidal hemorrhage contraindicated the anticoagulation. The main demographics, risk factors, clinical findings, neuroradiological characteristics, treatment and outcome of 10 consecutive patients with the diagnosis of CVST in a single public medical center in Costa Rica are described.